Toxic Stress: Effects, Prevention and Treatment - Hillary A. Franke (MDPI AG, 2014)
Children who experience early life toxic stress are at risk of long-term adverse health effects that may not manifest until adulthood. This article briefly summarizes the findings in recent studies on toxic stress and childhood adversity following the publication of the American Academy of Pediatrics (AAP) Policy Report on the effects of toxic stress. A review of toxic stress and its effects is described, including factors of vulnerability, resilience, and the relaxation response. An integrative approach to the prevention and treatment of toxic stress necessitates individual, community and national focus.